Nuclear envelope protein autoantigens in primary biliary cirrhosis - Worman, Howard J. (Hepatology research, 2007)
Antinuclear antibodies are detectable in approximately 50% of subjects with primary biliary cirrhosis (PBC). Most clinical laboratories use indirect immunofluorescence microscopy to detect antinuclear antibodies and two labeling patterns that predominate in PBC are nuclear rim and multiple nuclear dots. Antibodies giving these patterns most often recognize nuclear envelope protein gp210 and nuclear body protein sp100, respectively. Fewer subjects with PBC have autoantibodies giving nuclear rim labeling that recognize nucleoporin p62 and LBR. Gp210 is an integral protein localized to the nuclear pore membranes. Approximately 25% of subjects with PBC have detectable serum anti‐gp210 antibodies. The vast majority of anti‐gp210 antibodies from patients with PBC recognize a stretch of only 15 amino acids in the carboxyl‐terminal tail that faces the nuclear pore complex. Enzyme‐linked immunosorbent assays using either recombinant protein expressed in bacteria or chemically synthesized polypeptides have been established to reliably detect these autoantibodies. Although initial studies did not find a correlation between the presence of anti‐gp210 antibodies and prognosis in PBC, recent data suggest that the presence of antinuclear envelope protein antibodies correlate with an unfavorable disease course and more rapid progression.